Death in Anonymity: Population Dynamics and the Individual Within the Milwaukee County Poor Farm Cemetery, 1882–1925 - (:unkn) unknown (My University, 2018)
Prior to hospital construction in late 1991 and early 1992, and again in 2013, archaeologists were called upon to excavate 1,649 and 831 burials, respectively, from the unmarked Milwaukee County Poor Farm Cemetery. The individuals disinterred during these field seasons represent what remains of a much larger indigent population buried by Milwaukee County between 1882 and 1925 in what has been designated as Cemetery II. Long before the expanding facilities at Wauwatosa’s Milwaukee Regional Medical Center threatened these graves, however, the very nature of pauper burial grounds caused the identities of these disenfranchised individuals to be systematically obliterated. The research presented here is one component of the collaborative Milwaukee County Poor Farm Cemetery Project. My contribution to this important work is a project with the following complimentary goals: first, production of a comprehensive demography for the original burial population based on primary archival sources; second, the utilization of this demographic data and statistical testing to identify under- and overrepresented groups and provide contextual explanations for the relative frequency of these cohorts; third, contribution of aggregate data and procedures to the Milwaukee County Poor Farm Project’s burial identification efforts; and finally, construction of life history narratives for a small sample from the underrepresented groups to both demonstrate the utility of the archaeology of the individual approach and take small steps towards reversing the anonymity of this disenfranchised population. For many of Milwaukee’s late nineteenth- and twentieth-century residents, the pauper’s burial was an all-too-real possibility and a dreaded fate. If burial in a potter’s field was so loathsome, why were 7,226 individuals interred in the Milwaukee County Poor Farm Cemetery II? Poverty alone cannot be the answer, or this number would be even greater. Milwaukee’s lower class was substantial, but clearly most found the means to bury their dead elsewhere. A central theme in modern mortuary studies is that “the dead do not bury themselves but are treated and disposed of by the living” (Parker Pearson 199:3), so if we are to understand why an individual was buried in the poor farm cemetery, we must first have a sense of the social network in which he or she lived. What networks, then, could the deceased have relied upon to ensure a proper burial, and why did these fail? To elucidate these questions and satisfy the goals stated above, this project executes a multi-scalar research program. I first developed a full accounting of the MFPFC burial population utilizing various documentary resources. Second, I ran numerous goodness of fit chi-squared tests, comparing a temporally-controlled sample of City of Milwaukee death figures against the cemetery demography to determine which categories of individuals were under- or overrepresented in the burial population. Contextualizing these results within the city’s population history revealed the various social networks in which the dead participated during their lives and began to explain why these failed at keeping individuals from a pauper’s grave. The next step, matching the names from the documents to excavated burials, required a reduced scale of analysis and a synthesis of archaeological, osteological, and archival data. Finally, I constructed three life history narratives that highlight the archeology of the individual approach’s efficacy in illuminating failing social structures. Each case is unique and demonstrates that real value can be found in “seeing the trees through the forest.”
Keywords: Archaeology of the Individual; Archival Research; Demography; Historic Cemeteries; Life History; Milwaukee County